2018
DOI: 10.18699/vj18.376
|View full text |Cite
|
Sign up to set email alerts
|

GENDER-SPECIFIC INFLUENCE OF Aу MUTATION ON PROGENY METABOLIC PHENOTYPE, FETAL GROWTH AND PLACENTAL GENE EXPRESSION IN MICE

Abstract: Obesity during pregnancy increases the risk of obesity in offspring. To correct the offspring development in obese mothers, it is necessary to reveal the molecular mechanisms that mediate the influence of the maternal environment on the offspring ontogenesis. Leptin levels increase with obesity. In C57Bl mice, the Ау mutation is associated with elevated blood levels of leptin in pregnant females and exerts a gender-specific effect on the metabolic phenotype of mature offspring. Aim: to study the influence of А… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

4
3
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(7 citation statements)
references
References 37 publications
4
3
0
Order By: Relevance
“…However, in vivo experiments on leptin-treated pregnant mice and rats have shown that maternal leptin inhibits fetal growth [10,32]. Previously, we found that the weights of foetuses in mice with the A y mutation (this mutation increases the blood leptin levels during pregnancy [33]) were lower than those in the control mice on GD13 [34]. Our results are consistent with this previous finding and clearly demonstrate that maternal leptin inhibits fetal growth in mid-pregnancy.…”
supporting
confidence: 92%
See 4 more Smart Citations
“…However, in vivo experiments on leptin-treated pregnant mice and rats have shown that maternal leptin inhibits fetal growth [10,32]. Previously, we found that the weights of foetuses in mice with the A y mutation (this mutation increases the blood leptin levels during pregnancy [33]) were lower than those in the control mice on GD13 [34]. Our results are consistent with this previous finding and clearly demonstrate that maternal leptin inhibits fetal growth in mid-pregnancy.…”
supporting
confidence: 92%
“…Interestingly, in A y mice, elevated leptin levels were also associated with a decreased expression of Slc2a1 in the placentas of only female foetuses . Taken together, our results indicate that the elevation of blood leptin levels in mice in mid‐pregnancy sex‐specifically inhibits the expression of gene encoding GLUT1 in placentas.…”
Section: Discussionsupporting
confidence: 51%
See 3 more Smart Citations